2019
DOI: 10.1002/chem.201903880
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy for Through‐Bond Energy Transfer Fluorescence Probes Combining Intramolecular Charge Transfer: A Silyl Ether System for Endogenous Peroxynitrite Sensing

Abstract: Ag eneral strategy is reported for developing through-bond energy transfer (TBET) fluorescence probes by combining intramolecular charge transfer (ICT). The strategy uses ac oplanard onor-p-bridge-acceptor system (SiOPh-PyOH) without spirolactam. The off-on switcho fT BET and ICT is controlledb yc oplanar structurec hanges in the sensing process insteado fs pirolactam ring-opening in traditional TBET probes. DFT calculations showed that the energy and charget ransfers from SiOPh to PyOH are prohibited.Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Therefore, HOPyNa‐6‐OH can form an ionization equilibrium with ONOO − to give − OPyNa‐6‐OH and ONOOH (Scheme 3), and this equilibrium can be promoted by the decomposition of ONOOH to give more − OPyNa‐6‐OH , which is a weak fluorescent structure. Then, due to the further promotion by the decomposition of ONOOH, − OPyNa‐6‐OH can be further ionized to give − OPyNa‐6‐O − , which is a strong fluorescent system proved in the previous report, [9a] to achieve the ONOO − sensing. The density functional theory (DFT) calculations were carried out to confirm these fluorescence changes (Figure 5).…”
Section: Resultsmentioning
confidence: 69%
“…Therefore, HOPyNa‐6‐OH can form an ionization equilibrium with ONOO − to give − OPyNa‐6‐OH and ONOOH (Scheme 3), and this equilibrium can be promoted by the decomposition of ONOOH to give more − OPyNa‐6‐OH , which is a weak fluorescent structure. Then, due to the further promotion by the decomposition of ONOOH, − OPyNa‐6‐OH can be further ionized to give − OPyNa‐6‐O − , which is a strong fluorescent system proved in the previous report, [9a] to achieve the ONOO − sensing. The density functional theory (DFT) calculations were carried out to confirm these fluorescence changes (Figure 5).…”
Section: Resultsmentioning
confidence: 69%
“…In our previous report, we confirmed that ONOOH is a good reagent to remove silyl ether protection and give − ONNO − in the presence of excessive ONOO − (>6 eq. ), which give a green fluorescence emission (Figure a, d). When the concentration of ONOO − is 2–6 eq., the probe emits an orange or yellow fluorescence emission, a mixed color by pink and green (Inset in Figure c).…”
Section: Methodsmentioning
confidence: 99%